Physical principle dealing with development of vortices formed by DBD actuator - Procházka P.; Uruba V. (EPJ Web of Conferences, 2014)
Several configurations of vortex trains generated by plasma dielectric barrier discharge were measured by method of time-resolved PIV with application of phase-averaging of data. Mainly dynamics of vortical structures was studied in terms of vortex core trajectory, convective velocity, vortex diameter and vortex circulation. The generally valid physical mechanism of such vortices based on gained information will be introduced and presented. This mechanism will be considered with regards to the use for active flow control thus it could be very helpful in the future works dealing with plasma flow control.